A randomized, double-blind, phase III study comparing two doses of erlotinib for second-line treatment of current smokers with advanced non-small-cell lung cancer (CurrentS). (September 2016) - Smit, Egbert F.; Wu, Yi-Long; Gervais, Radj; Zhou, Caicun; Felip, Enriqueta; Feng, Jifeng; Guclu, Salih Zeki; Hoiczyk, Mathias; Dorokhova, Elena; Freudensprung, Ulrich; Grange, Susan; Perez-Moreno, Pablo Diego; et al.
Highlights: CurrentS assessed erlotinib 300 mg/day vs 150 mg/day in current smokers with NSCLC. Median PFS and OS were 7.0 vs 6.9 weeks and 6.8 months vs 6.8 months (E300 vs E150). E300 resulted in higher mean erlotinib plasma concentrations vs the E150 dose. 89.2% (E300) and 84.4% (E150) had ≥1 any grade AE (44.3% and 37% had grade ≥3 AEs). There was no efficacy benefit of a 300 mg dose versus the 150 mg dose in smokers. Abstract: Objectives: Active smokers with non-small-cell lung cancer (NSCLC) have increased erlotinib metabolism versus non-smoking patients, which reduces exposure. Therefore, an increased erlotinib dose may be beneficial. The CurrentS study (NCT01183858) assessed efficacy and safety of 300 mg erlotinib (E300) as second-line therapy in current smokers with locally advanced or metastatic NSCLC versus the standard 150 mg dose (E150). Materials and methods: Patients with stage IIIB/IV NSCLC (current smokers who failed first-line platinum-based chemotherapy) were randomized to receive E150 or E300 until progression/death/unacceptable toxicity. Primary endpoint: progression-free survival (PFS). Secondary endpoints: overall survival (OS), disease control rate and safety. Results: A total of 342 patients were screened; the intent-to-treat population comprised 159 E300 patients and 154 E150 patients. Median PFS was 7.0 versus 6.9 weeks with E300 versus E150, respectively (unstratified hazard ratio [HR] = 1.05, 95% confidence interval [CI]: 0.83–1.33; unstratified log-rank P  = 0.671). Median OS was 6.8 months in both arms (unstratified HR = 1.03, 95% CI: 0.80–1.32; unstratified log-rank P  = 0.846). Overall, 89.2% (E300 arm) and 84.4% (E150 arm) experienced ≥1 adverse event (AE) of any grade (44.3% and 37%, respectively, experienced grade ≥3 AEs); AEs of special interest were reported in 67.7% and 47.4% of patients, respectively. E300 resulted in higher mean plasma concentrations versus E150, however, this did not improve efficacy. Conclusions: Despite the difference in erlotinib exposure, there was no evidence of an incremental efficacy benefit of a higher erlotinib dose versus the standard dose in this population of highly active smokers.